Biological activities of isolated compounds from vitex negundo leaf - Chowdhury, NY; Islam, W; Khalequzzaman, M (Journal of Bio-Science, 2011)
Context: Viyex negundo Linn. (Verbenaceae) is a beautiful tree which is an erect, large aromatic shrub with quadrangular branchlets possess pesticidal, antibacterial and antifungal properties. Objective: To determine the biological activities (antibacterial, antifungal, brine shrimp lethality bioassay) of the two isolated compounds from methanolic leaf extract. Materials and Methods: Powdered leaves of nishinda were extracted with methanol using Soxhlet’s apparatus and subsequent analyses isolated two compounds. Five gram-positive, eight Gram-negative bacterial strains were used for the antibacterial activity using the disc diffusion assay method. The antifungal activities of the isolated compounds were also performed on four pathogenic fungi. Each pure compound was dissolved in 200 μl of methanol to get a concentration 300 μg/10 μl. Minimum Inhibitory Concentrations were determined by serial dilution technique. For brineshrimp bioassay each compound and standard amphicilin trihydrate were dissolved in dimethylsulfoxide to get a five concentrations. Each concentration contained three vials consisting of 10 nauplii in 5 ml of treated sea water. The number of survived nauplii were counted after 24 h and the LD50 values were calculated. Results: The zone of inhibition was prominent for the control (kanamycin) at concentration of 30 μg/disc. At 100 μg/disc Compound 1 exhibited bigger and more prominent clear zone of growth inhibition in all test microorganisms except Shigella shiga. On the contrary, Compound 2 at 100 μg/disc, showed clear zone of inhibition in all bacteria, but inhibition of zones were larger in Compound 1 than Compound 2. Antimicrobial effect of Compound 2 tested on different pathogenic bacteria (MIC 128 μg/ml) and fungi showed that it possesses growth inhibitory effect at various concentrations. MIC of Compound 1 for B. subtilis, S. aureus and S. B-haemolyticus was 64 μg/ml, whereas for P. aeruginosa it was 128 μg/ml (Table 2). MIC of Compound 2 was 128 μg/ml for B. subtilis, S.-β-haemolyticus and P. aeruginosa whereas it was 64 μg/ml for S. aureus. No fungal activity was observed for Compound 1. Clear inhibition zone was observed for Compound 2 at both concentrations for all of the pathogenic fungi tested. At 100 μg/disc Compound 2 exhibited bigger and prominent clear zone than 50 μg/disc.. Brine shrimp bioassay showed the toxic effect of the both the compounds. Conclusion: The findings indicate promising antibacterial and antifungal activities of V. negundo against life treating pathogens which appears to be an effective material for development of antimicrobial drugs and ecofriendly biopesticides. Keywords: Vitex negundo; Antimicrobial; MIC; bacteria; phytochemical; medicinal plant activity; brineshrimp DOI: http://dx.doi.org/10.3329/jbs.v18i0.8776 JBS 2010; 18(0): 53-59